Defining the Innate Immune Responses for SARS-CoV-2-Human Macrophage Interactions - Abdelmoaty, Mai M.; Yeapuri, Pravin; Machhi, Jatin; Olson, Katherine E.; Shahjin, Farah; Kumar, Vikas; Zhou, You; Liang, Jingjing; Pandey, Kabita; Acharya, Arpan; Byrareddy, Siddappa N.; Mosley, R. Lee; et al. (Frontiers in Immunology, 2021)
Host innate immune response follows severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, and it is the driver of the acute respiratory distress syndrome (ARDS) amongst other inflammatory end-organ morbidities. Such life-threatening coronavirus disease 2019 (COVID-19) is heralded by virus-induced activation of mononuclear phagocytes (MPs; monocytes, macrophages, and dendritic cells). MPs play substantial roles in aberrant immune secretory activities affecting profound systemic inflammation and end-organ malfunctions. All follow the presence of persistent viral components and virions without evidence of viral replication. To elucidate SARS-CoV-2-MP interactions we investigated transcriptomic and proteomic profiles of human monocyte-derived macrophages. While expression of the SARS-CoV-2 receptor, the angiotensin-converting enzyme 2, paralleled monocyte-macrophage differentiation, it failed to affect productive viral infection. In contrast, simple macrophage viral exposure led to robust pro-inflammatory cytokine and chemokine expression but attenuated type I interferon (IFN) activity. Both paralleled dysregulation of innate immune signaling pathways, specifically those linked to IFN. We conclude that the SARS-CoV-2-infected host mounts a robust innate immune response characterized by a pro-inflammatory storm heralding end-organ tissue damage.